FGFR2 expression relates to subtype-specific tumour microenvironment (TIME) during luminal breast cancer evolution - Sołek, Julia; Zielińska, Aleksandra; Kordek, Radzisław; Romańska, Hanna; Braun, Marcin (Frontiers in Oncology, 2025)
BackgroundFibroblast growth factor receptor 2 (FGFR2) is an oncogenic driver in luminal breast cancer (BCa), with emerging evidence linking it to tumour immune microenvironment (TIME) modulation. While FGFR2’s role in endocrine resistance is established, its potential involvement in shaping immune infiltration—particularly in the transition from ductal carcinoma in situ (DCIS) to invasive ductal carcinoma (IDC)—remains underexplored.MethodsThis retrospective study analysed 99 BCa specimens collected between 2004–2019. Immunohistochemistry was used to assess FGFR2 expression and immune markers (CD8, CD68, CD163, FOXP3). Clinical and pathological variables were evaluated, and immune cell densities were compared across disease stages and BCa subtypes (luminal vs. non-luminal). Correlations between FGFR2 expression and immune markers were assessed using non-parametric statistical tests.ResultsProgression from DCIS to IDC was associated with increased infiltration by CD8+ T cells and CD68+ macrophages. FGFR2 expression showed differences between DCIS and IDC with an extensive DCIS component and was positively correlated with CD8+, CD163+, and FOXP3+ cell densities. The latter associations were exclusive to luminal A tumours, with no such correlations observed in non-luminal subtypes.ConclusionsFGFR2 expression in luminal A BCa correlates with markers of immunosuppressive TIME, particularly CD163+ macrophages and FOXP3+ T cells. These subtype-specific interactions suggest a synergistic role of FGFR2 and estrogen receptor signalling in immune evasion and tumour progression, warranting further mechanistic and therapeutic investigation. However, the small number of cases in certain subgroups, particularly DCIS and non-luminal tumours, limits the generalizability of these findings and warrants cautious interpretation.